The Effect of Drying Method on The Quality of MOCAF (Modified Cassava Flour) from Raw Material Beta-Carotene-Rich Bokor Genotype Cassava - Aprilia, Aqsha Putri; Fathoni, Rois; Fathoni, Ahmad; Setiarto, Raden Haryo Bimo; Damayanti, Ema (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
The high dependence on flour imports is a significant challenge to overcome by processing local food ingredients through diversification. To address this challenge, the use of MOCAF (Modified Cassava Flour) as a substitute for wheat flour has been carried out in the manufacture of wet and dry noodles, along with analog rice, and bread. The optimization of MOCAF production from beta-carotene-rich cassava depends on the selection of appropriate equipment technology and drying process. Therefore, this study aimed to analyze the effect of drying method on MOCAF characteristics of beta-carotene-rich cassava genotype. The analysis was carried out using two methods, namely sun drying for 3-4 days and oven drying at 60 o C for 24 hours. Parameters analyzed included viscosity, solubility, syneresis, Near Infra-Red analysis, proximate analysis, and Scanning Electron Microscope (SEM). The results showed that drying affected the physicochemical properties of MOCAF, including viscosity, solubility, and syneresis. NIR (Near-infrared) and proximate analysis showed that drying process affected the decrease in moisture, ash, protein, and fat content, along with an increase in crude fiber, and dry fiber matter content. Furthermore, SEM microstructural analysis resulted in the reformation of starch granules, characterized by changes in morphology and structure, such as the separation of irregular spherical shapes, and hollowness.